What Is a Lineage?. Issue 4 (December 2019) - Neto, Celso
Abstract : This article defends lineage pluralism; the view that biological lineages are not a single, unified type of entity. I analyze aspects of evolutionary theory, phylogenetics, and developmental biology to show that these areas appeal to distinct notions of lineage. I formulate three arguments for lineage pluralism. These arguments undercut the main motivations for lineage monism; the view that biological lineages are a single, unified type of entity. Although this view is rarely made explicit, it is often assumed in philosophy and biology. Hence, this article sheds light on this monistic assumption and shows why lineage pluralism should be adopted instead.